Scope and potential of hortipastoral systems for enhancing livestock productivity in Jammu and Kashmir - Ahmad, Suheel; Khan, P.A.; Verma, D.K.; Mir, Nazim; Singh, J.P.; Dev, Inder; Roshetko, James M. (Indian Journal of Agroforestry, 2020)
Agroforestry is one of the sustainable approaches to land-use management where both agricultural crops and tree crops combine into an integrated production system to get maximum benefits. Yield and quality of forage in agroforestry systems can be improved by introducing shade-tolerant grass (Dactylis glomerata, Festuca arundinaceae, Phleum pratense, Setaria spp etc.) and legume species (Trifolium pratense, Trifolium repens, Medicago sativa etc.) in appropriate mixtures. Management of these systems can present a challenge especially in the selection of proper grass and legume species as well as the maintenance of the optimum balance between the two species in the grass–legume stand. Livestock plays very vital role in the economic development of the state of Jammu and Kashmir and forms an integral part of state agriculture. However, the major challenge is to bridge the gap between forage production and requirement. The state produces around 64 lakh MT of green fodder and 35 lakh MT of dry fodder. However the requirement of green is 139.13 lakh MT and dry is 58.53 lakh MT. Therefore, increased production of fodder is essential to meet the nutritional requirements of the livestock. The resource base available with the farming community is limited. Limited land endowments make it further difficult for the farmers to earmark adequate land for fodder and forage cultivation. Estimates of Horticulture Department of Jammu and Kashmir state are more than 340 thousand hectares under orchards wherein there is a scope for the introduction of fodder crops as inter-crop. Hortipastoral system, therefore, seems to be the possible solution not only in meeting the continuous increase in the demand for fruit and fodder but also in improving the productivity and sustainability of the system as a whole. An attempt has been made to review the forage potential status, livestock resource and suggest the potential for augmentation of forage production.